2014
DOI: 10.1530/joe-13-0447
|View full text |Cite
|
Sign up to set email alerts
|

GH administration patterns differently regulate epidermal growth factor signaling

Abstract: Current GH administration protocols imply frequent s.c. injections, resulting in suboptimal compliance. Therefore, there is interest in developing delivery systems for sustained release of the hormone. However, GH has different actions depending on its continuous or pulsatile plasma concentration pattern. GH levels and circulating concentration patterns could be involved in the regulation of epidermal growth factor receptor (EGFR) expression in liver. Aberrant expression of this receptor and/or its hyperactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
2
9
1
Order By: Relevance
“…GH-overexpressing transgenic mice showed increased EGFR hepatic levels (González et al 2010) but reduced or similar EGF induction of c-MYC, c-JUN, c-FOS and CYCLINs with respect to normal siblings. These results are different from those described for normal mice receiving intermittent injections of GH during a short period (Díaz et al 2014). In that case, the treatment induced a significant upregulation of the receptor and, concomitantly, an increased expression of early genes involved in cell cycle control.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…GH-overexpressing transgenic mice showed increased EGFR hepatic levels (González et al 2010) but reduced or similar EGF induction of c-MYC, c-JUN, c-FOS and CYCLINs with respect to normal siblings. These results are different from those described for normal mice receiving intermittent injections of GH during a short period (Díaz et al 2014). In that case, the treatment induced a significant upregulation of the receptor and, concomitantly, an increased expression of early genes involved in cell cycle control.…”
Section: Discussioncontrasting
confidence: 91%
“…In that case, the treatment induced a significant upregulation of the receptor and, concomitantly, an increased expression of early genes involved in cell cycle control. The difference between both models is the nature of GH influence over EGF signaling pathways; chronic and continuous circulating GH levels caused an upregulation of EGFR liver content but a desensitization of EGF signaling (González et al 2010, Díaz et al 2012, whereas short-term treatment with intermittent injections of EGF also produced an increase in EGFR protein content but upregulated EGF signaling (Díaz et al 2014). Therefore, the next goal was to elucidate possible mechanisms involved in the attenuation of EGF signal in the liver of transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further support to the idea that the liver of our double-KO mice model had partial resistance to GH actions was obtained by measuring hepatic egf-r expression, a molecular marker reported to be highly sensitive to GH levels and to the pattern of GH delivery, and to be associated to liver resistance. In fact, Diaz et al (23) recently reported that continuous GH delivery in male mice suppresses egf-r, which was associated with a loss of hepatic GH responsiveness as observed in models with low GH levels [ie, ob/ob (24)]. Accordingly, double-SST/ CORT-KO mice with elevated GH levels in a feminized pattern displayed a markedly reduced hepatic egf-r expression, which would likely be accompanied by reduced hepatic GH responsiveness/partial GH resistance that may explain the lack of an IGF-1 rise in a model with high GH levels.…”
Section: Discussionmentioning
confidence: 99%